2010
DOI: 10.1002/ca.21087
|View full text |Cite
|
Sign up to set email alerts
|

Sacralization is not associated with elongated cervical costal process and cervical rib

Abstract: Cervical rib/elongated costal process of the seventh cervical vertebra and sacralization of a lumbar vertebra are associated with clinical problems-neurological, vascular, and obstetrical. A previous study reported an association between these morphologies, and suggested that clinicians use presence of one trait to predict presence of the other. This study tested three hypotheses from this association: costal process length among individuals with sacralization differs from that among individuals without sacral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…We are unaware of any reports on the proportion of anomalous presence of anterior tubercles at the C7 transverse process with which to compare our finding of approximately 1%. Our finding that approximately 0.3% (7/2067 patients) had cervical ribs at the C7 transverse process is similar to the findings in previous reports of 0.42% (13), 0.74% (14), 0.87% (15), and 6.1% (11). We do not have an explanation for the difference between our result and that of Erkin et al.…”
Section: Discussionsupporting
confidence: 91%
“…We are unaware of any reports on the proportion of anomalous presence of anterior tubercles at the C7 transverse process with which to compare our finding of approximately 1%. Our finding that approximately 0.3% (7/2067 patients) had cervical ribs at the C7 transverse process is similar to the findings in previous reports of 0.42% (13), 0.74% (14), 0.87% (15), and 6.1% (11). We do not have an explanation for the difference between our result and that of Erkin et al.…”
Section: Discussionsupporting
confidence: 91%
“…I chose the costal facet as a principal criterion for distinguishing thoracic and lumbar vertebrae for two reasons. First, this project is one of a series of projects dealing with the costal process (Tague, ). Second, absence or presence of a costal facet is a nominal variable, whereas zygapophyseal orientation is an interval variable.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that 60% of the cases with sacrococcygeal fusion were not associated with TLTV. The reported prevalence in literature of sacrococcygeal fusion ranges between 0 to 71.7% [40]. Thus, the result is not surprising, as sacrococcygeal fusion specifically refers to the ankylosing of the coccyx to the sacrum [41,42].…”
Section: Discussionmentioning
confidence: 99%